THREE-DIMENSIONAL TOMOGRAPHIC RECONSTRUCTION OF FOUNDRY ARTICLES ON LIMITED MODEL AND EXPERIMENTAL DATA - V. L. Vengrinovich; S. A. Zolotarev (Литьë и металлургия, 2009)
The ways of overcoming of lack of source information, The ways of overcoming of lack of source information, allowing to reduce energy of primary X-radiation, necessary  for radiography and to provide high quality of reconstruction, are offered.